Inequality measurement with subgroup decomposability and level-sensitivity - Subbu Subramanian (Economics: The Open-Access, Open-Assessment E-Journal, 2011)
Subgroup Decomposability is a very useful property in an inequality measure, and level-sensitivity, which requires a given level of inequality to acquire a greater significance the poorer a population is, is a distributionally appealing axiom for an inequality index to satisfy. In this paper, which is largely in the nature of a recollection of important results on the characterization of subgroup decomposable inequality measures, the mutual compatibility of subgroup decomposability and level-sensitivity is examined, with specific reference to a classification of inequality measures into relative, absolute, centrist, and unit-consistent types. Arguably, the most appealing combination of properties for a symmetric, continuous, normalized, transfer-preferring and replication-invariant (S-C-N-T-R) inequality measure to satisfy is that of subgroup decomposability, centrism, unit-consistency and level-sensitivity. The existence of such an inequality index is (as far as this author is aware) yet to be established. However, it can be shown, as is done in this paper, that there does exist an S-C-N-T-R measure satisfying the (plausibly) next-best combination of properties - those of decomposability, centrism, unit-consistency and level-neutrality.
Keywords: D30; D31; D63; 330; subgroup decomposability; level-sensitivity; absolute inequality measure; relative inequality measure; centrist inequality measure; unit-consistency